María Elena Placencia y Carmen García (eds). Research on politeness in the Spanish Speaking World. Mahwah, New Jersey/ London: Lawrence Erlbaum Associates, 2007 442 págs. ISBN 978-0-8058-5227-1 - Grisolía, María Belén (Discurso & Sociedad, 2008)
María Elena Placencia y Carmen García (eds). Research on politeness in the Spanish Speaking World. Mahwah, New Jersey/ London: Lawrence Erlbaum Associates, 2007 442 págs. ISBN 978-0-8058-5227-1.